Risk factors for dengue mortality: a 7-year retrospective cohort in Honduras - Dilcia Sauceda-Acosta; Sandra Paola Paz Almendares; Elsy Cárcamo; Melba Zúniga-Gutiérrez; Briana Beltrán; María Félix Rivera; Marlon Meléndez Rodríguez; Judy Enamorado (BMC Infectious Diseases)
Abstract Background Dengue is the viral disease with the highest morbidity and mortality rates worldwide. The aim of this study was to describe the epidemiological trends of dengue cases and dengue death cases and identify the demographic, clinical and laboratory risk factors for dengue mortality in Honduras. Methods A retrospective cohort study of suspected cases of dengue between 2016 and 2022 was conducted. Patients of the 18 departments of the country were included. Patients were classified as deceased and alive. In the univariate analysis, normality test was assessed. In bivariate analysis, the chi-square and Mann Whitney U tests were used as appropriate. Crude odds ratios (cOR) with their respective 95% confidence intervals (CIs), were estimated to determine the risk of death due to dengue. In multivariate analysis, a logistic regression model was built. Results A total of 23,811 suspected cases of dengue were recorded, of which 14,927 tested positive, resulting in 242 deaths. The predominant sex among both deceased and surviving patients was female, 54.1% and 54.2%, respectively. Among the deceased, the largest age group was 5–9 years (32.6%), followed by 20–49 years (26.9%). Among surviving patients, the largest age groups were 20–49 years (28.9%) and 10–19 years (28.2%). Francisco Morazán reported the most dengue cases, while Cortés had the highest dengue deaths. Risk factors for dengue mortality included older age (> 60 years; adjusted OR 3.30, 95% CI 1.08–10.09), residence in the departments of Choluteca (aOR 19.40, 95% CI 4.75–79.30), Cortés (aOR 6.57, 95% CI 2.00–21.47), and Yoro (aOR 10.80, 95% CI 2.97–39.26), clinical manifestations of bleeding (aOR 1.81, 95% CI 1.09–3.00), clinical manifestations of plasma leakage (aOR 1.72, 95% CI 1.53–1.93), shock (aOR 10.70, 95% CI 7.90–14.50), lethargy (aOR 1.80, 95% CI 1.25–2.59), presence of comorbidities (aOR 1.89, 95% CI 1.08–3.29), and pregnancy (aOR 2.18, 95% CI 1.37–3.48). Conclusion Older age; residence in the departments of Choluteca, Cortés, and Yoro; clinical manifestations of bleeding, plasma leakage, shock, lethargy; comorbidities and pregnancy were identified as risk factors for dengue mortality. Early identification of risk factors can help recognize patients who require close and timely clinical monitoring, which could improve outcomes in terms of reducing dengue mortality.